Do Individuals Adapt to All Types of Housing Transitions? - Andrew E. Clark; Luis Diaz-Serrano (Institute of Labor Economics (IZA), 2022)
This paper provides one of the first tests of adaptation to the complete set of residential transitions. We use long-run SOEP panel data and consider the impact of all housing transitions, whether or not they involve a change in housing tenure or geographical movement, on both life satisfaction and housing satisfaction. Controlling for individual characteristics, some residential transitions affect life satisfaction only little, while all transitions have a significant effect on housing satisfaction. This latter is particularly large for renters who become homeowners and move geographically, and for renters who move without changing tenure status. Regarding housing satisfaction, we only uncover evidence of some adaptation for renter-renter moves. Losing homeowner status is the only transition that produces lower housing satisfaction, and here the effect seems to become even more negative over time.
Keywords: D19; R21; 330; well-being; adaptation; housing; SOEP